Association between migraine and epilepsy: a meta-analysis - Wu, Xiaohui; Zhuang, Jiaxin (Frontiers in Neurology, 2024)
Background Epidemiological studies have demonstrated a comorbid association between migraine and epilepsy. However, despite the long history of this association, the exact nature of the relationship between migraine and epilepsy remains largely unresolved. Therefore, it is crucial to conduct a meta-analysis in order to thoroughly investigate the relationship between migraine and epilepsy. Methods Odds ratios (ORs) or relative risks (RRs) and 95% confidence intervals (CIs) regarding association between migraine and epilepsy were summarized using STATA 12.0 software. Results There was an 80% increase in the lifetime prevalence of migraine among patients with epilepsy, compared to those without epilepsy with a random effects model (OR/RR: 1.80, 95% CI: 1.35 to 2.40, I2 = 97.5%, p < 0.001). There was an 80% increase in the lifetime prevalence of epilepsy among patients with migraine, compared to those without migraine with a random effects model (OR/RR: 1.80, 95% CI: 1.43 to 2.25, I2 = 80.6%, p < 0.001). Conclusions It is important to note the comorbid association between migraine and epilepsy examined in the study.